Analisis Butir Soal Ujian Madrasah Bahasa Indonesia Berdasarkan Tingkat Berpikir Siswa di KKM 1 Garut - Komariah, Iis; Agus Hamdani; Nizar Alam Hamdani; Encep Suherman; Ari Kartini (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This study aims to analyze the madrasah exam questions based on the level of thinking of students. The discussion in this study includes the level of effectiveness of the sentences in the questions, the validity of the questions, the reliability and level of difficulty, the discriminating power index, the effectiveness of deceptive items and grouping questions based on the thinking levels of Order Thinking Skills (LOTS), Middle Order Thinking Skills (MOTS), and Higher Order. Thinking Skills (HOTS). The research conducted included descriptive research types of document analysis. The documents analyzed were grid documents, Indonesian language madrasa exam questions at MTsN 1 Garut which consisted of 35 multiple choice questions and 5 descriptions and answer sheets for examinees. The results obtained based on the research that has been done are as follows. First, the sentences used in the Indonesian language madrasa exam questions at MTsN 1 Garut already use effective sentences. Second, the validity of the questions shows that there are 23 valid questions and 17 invalid questions. Third, the reliability level of multiple choice questions is high, while the description questions are in the moderate category. Fourth, the difficulty level of the questions is 14 questions in the easy category, 4 questions in the medium category, and 14 questions in the high category. Fifth, the level of discrimination is 8 low categories, 18 medium categories, and 14 high categories. Sixth, the effectiveness of the distractor, as many as 15 questions function properly and 20 questions do not function properly. It contains 1 question in the Level Order Thinking Skills (LOTS) category, 19 questions in the Middle Order Thinking Skills (MOTS) category, and 20 questions in the Higher Order Thinking Skills (HOTS) category.